Complex Case Of Copd Exacerbation With Lung Cancer And Paraneoplastic Syndrome: A Case Report - Syazili Mustofa; Faizah Zahrah Sidik; Evi Kurniawaty; Miftahur Rohman; Nisa Karima (Jurnal Ilmu Kedokteran dan Kesehatan, 2026)
Managing Chronic Obstructive Pulmonary Disease (COPD) alongside advanced lung cancer is highly complex, especially when complicated by multiple paraneoplastic syndromes. We present a 70-year-old male with shortness of breath, hemoptysis, and significant weight loss. Evaluation revealed an acute COPD exacerbation unmasking a metastatic right lung cancer with a rare combination of concurrent paraneoplastic syndromes (anemia, hyponatremia, and hypocalcemia). The uniqueness of this case lies in how these overlapping systemic manifestations masked the acute respiratory exacerbation, creating a profound diagnostic dilemma. Clinically, this implies that physicians must maintain a high index of suspicion for underlying malignancies when treating atypical or refractory COPD exacerbations. The key lesson learned is that managing such intertwined conditions requires prompt, individualized, and multidisciplinary coordination to prevent delayed interventions and optimize patient outcomes.